Characterizing cardiac autonomic dynamics of fear learning in humans. (7th June 2022) - Battaglia, Simone; Orsolini, Stefano; Borgomaneri, Sara; Barbieri, Riccardo; Diciotti, Stefano; di Pellegrino, Giuseppe
Abstract: Understanding transient dynamics of the autonomic nervous system during fear learning remains a critical step to translate basic research into treatment of fear‐related disorders. In humans, it has been demonstrated that fear learning typically elicits transient heart rate deceleration. However, classical analyses of heart rate variability (HRV) fail to disentangle the contribution of parasympathetic and sympathetic systems, and crucially, they are not able to capture phasic changes during fear learning. Here, to gain deeper insight into the physiological underpinnings of fear learning, a novel frequency‐domain analysis of heart rate was performed using a short‐time Fourier transform, and instantaneous spectral estimates extracted from a point‐process modeling algorithm. We tested whether spectral transient components of HRV, used as a noninvasive probe of sympathetic and parasympathetic mechanisms, can dissociate between fear conditioned and neutral stimuli. We found that learned fear elicited a transient heart rate deceleration in anticipation of noxious stimuli. Crucially, results revealed a significant increase in spectral power in the high frequency band when facing the conditioned stimulus, indicating increased parasympathetic (vagal) activity, which distinguished conditioned and neutral stimuli during fear learning. Our findings provide a proximal measure of the involvement of cardiac vagal dynamics into the psychophysiology of fear learning and extinction, thus offering new insights for the characterization of fear in mental health and illness. Abstract : Understanding transient dynamics of the autonomic nervous system during fear learning remains a critical step to translate basic research into treatment of fear‐related disorders. Here, using a novel frequency‐based analysis to capture transient changes of heart rate variability, our findings highlight a selective modulation of the high frequency (HF) band of the power spectrum, when facing fear‐relevant stimuli. Crucially, these results reveal specific increased parasympathetic (vagal) activity during fear learning in humans.